PENERAPAN METODE QUIZ BERBASIS MICROSOFT FORM UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK SISWA KELAS V SDN DUKUH MENANGGAL I/424 SURABAYA - Maria Christina Sri Sunarsih (Universitas Negeri Surabaya, 2022)
One of the implementations of the use of information and communication technology in education can be realized through online learning. With the implementation of Work From Home (WFH) it becomes a challenge for teachers to still be able to create fun, interesting, and active learning. Quiz method based on microsoft form can help teachers in carrying out evaluations. The problems to be studied in this research are: (a) the application of the Microsoft Form-based Quiz method to improve thematic learning outcomes for fifth grade students at SDN Dukuh Menanggal I/424 Surabaya in the 2020/2021 academic year? (b) How is the improvement of thematic learning learning outcomes after applying the Microsoft Form-based Quiz method to class V students at SDN Dukuh Menanggal I/424 Surabaya in the 2020/2021 school year?. The objectives of this action research are: (a) Want to know the application of the Microsoft Form-based Quiz method to improve thematic learning outcomes. (b) Want to know the improvement of thematic learning outcomes after applying the Microsoft Form-based Quiz method. This study uses two rounds of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is the fifth grade students of SDN Dukuh Menanggal I/424 Surabaya in the 2020/2021 academic year with a total of 39 students. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement increased from cycle I to cycle II, namely, cycle I (79.49%), cycle II (92.31%). The conclusion of this study is that the Microsoft Form-based Quiz method can have a positive effect on improving student learning outcomes for class V SDN Dukuh Menanggal I/424 Surabaya in the 2020/2021 school year, and this learning method can be used as an alternative thematic learning.